Serotonin Transporter (5-HTT) Gene Polymorphisms and Susceptibility to Chronic Periodontitis: A Case-Control Study - Wu, Lan; Deng, Tong; Wang, Chao-Yang; Ren, Xue-Qun; Wang, Yun-Yun; Zeng, Xian-Tao; Geng, Pei-Liang (Frontiers in Genetics, 2019)
Objective: The current study was aimed to explore the relationship between chronic periodontitis and serotonin transporter (5-HTT) gene polymorphisms (rs6354 and rs12449783) in Chinese Han population. Methods: This study included a total of 120 patients with chronic periodontitis and 125 healthy control subjects. The 5-HTT gene (rs6354 and rs12449783) was genotyped using oral mucosal tissue with polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Linkage disequilibrium was examined using Haploview. Genotype and allele frequency were compared between the cases and controls using 2 test. Results: Genotype distribution of 5-HTT gene polymorphisms rs6354 and rs12449783 in the control group conformed to HWE. The frequency of AC genotype, AC+CC genotype and C allele of 5-HTT rs6354 polymorphism was higher in cases (P<0.05 vs. the healthy control. Adjusted odds ratio (OR) was 1.910 (95%CI =1.049-3.476) for the AC genotype, 2.026 (95%CI=1.115-3.680) for the AC+CC genotype, and 1.875 for the C allele (95%CI =1.089-3.228. Such an association was particularly strong in women for AC genotype (OR = 2.167, 95%CI = 1.034-4.542). The genotypes and alleles frequencies of rs12449783 did not differ between the cases and controls. Haplotype C-C (rs6354-rs12449783) was also more frequent in the cases (OR=2.372, 95%CI=1.154-4.875, P=0.016). Conclusion: Chronic periodontitis is associated with 5-HTT gene rs6354 polymorphism, as well as rs6354/rs12449783 interaction.